ANALISIS PENERAPAN AKUNTANSI SYARIAH BERDASARKAN PSAK 402 PADA PEMBIAYAAN MURABAHAH DI KOPERASI SYARIAH SERBA USAHA SALIMAH JAMBI - Jamiah, Jamiah; Mellya Embun Baining; Laily Ifazah (Nusantara Hasana Journal, 2026)
The background of this research focuses on the importance of implementing sharia accounting based on the provisions of PSAK 402. This study aims to analyze the application of sharia accounting based on PSAK 402 in murabahah financing and identify obstacles that often occur in murabahah financing at the Salimah Multipurpose Sharia Cooperative. This study uses a qualitative method with a descriptive approach. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study indicate that the application of murabahah financing accounting at the Salimah Multipurpose Sharia Cooperative is not fully in accordance with the provisions of PSAK 402. The inconsistency is found in the aspects of recognition and measurement, as well as presentation. Where the Salimah Multipurpose Sharia Cooperative does not apply fines, down payments, realization of receivables, and presentation of murabahah expenses. However, in the disclosure aspect, the application of murabahah financing accounting is in accordance with the provisions of PSAK 402. The obstacle that often occurs in murabahah financing at the Salimah Multipurpose Sharia Cooperative is the existence of problematic financing. Problematic financing occurs because, of all customers or members served, some members fail to fulfill their monthly mandatory savings obligations. This study concludes that sharia accounting practices in cooperatives are quite good, but not yet fully compliant with PSAK 402 standards and therefore require improvement.